First-principles Electronic Structure Calculation of Topological Insulator Bi2Te3 - P., Taivansaikhan; N., Tsogbadrakh; S.C., Hong (Scientific transaction of the National University of Mongolia. Physics, 2022)
Bismuth telluride (Bi2Te3) attracts much attention as a topological insulator. Using the first-principles density-functional calculations based on generalized gradient approximation, the structural and electronic properties of Bi2Te3 have been done with and without spin-orbit coupling (SOC). Total energy calculations showed that the optimized lattice parameters are a= b= 4.44 Å and c= 32.20 Å, in consistent with an experiment. Bi2Te3 is calculated to be an insulating with band gap of 0.5 eV from the density of states without SOC. Finally, we found that the effect of SOC is a crucial to determine the experimentally observed very narrow band gap of 0.15 eV.